Integrative Pharmacotherapy Teaching with Objective Structured Pharmacotherapy Examination - Abraham Simatupang; Mulyadi Djojosaputro; Roma Tobing; Hertina Silaban; Lili Indrawati (Universitas Padjadjaran, 2020)
Writing an appropriate prescription is one of the main competencies of medical doctors. Studies reveal that medication error is still a significant issue in health service, and many efforts have been done to minimise this through trainings. Integrative pharmacotherapy is a module delivered for medical students in clinical clerkship, which is adopted and developed from the World Health Organization Guide to Good Prescribing. The aim of the study was to examine the effect of the module on pre-test and post-test scores which consists of 17 clinical cases. The study was done in the Faculty of Medicine, Universitas Kristen Indonesia, East Jakarta from July to November 2018. Eighty one subjects were randomly selected from the data of 100 students who were screened from 200 students based on the exclusion criteria. There was an increase of post-test score which was statistically significant compared to pre-test score, from 42.07±12.45 to 58.47±8.54 (p=0.000, CI -19.36;-13.45). There were 69 (>85%) students having grade D and E in pre-test, but the number decreased to 18 (22,2%) out of 81 subjects in post-test. Both grade C and B students increased from 13.5% to 70.4% and 1% to 7%, respectively. Most of the students were first entries into clinical clerkship, thus, their pre-test scores were very low since they had not had the clinical experience yet. However, at the end of the clerkship, there was a significant increase on their knowledge on pharmacotherapy and prescription for particular diseases. An outcome study to measure the retention and to examine their success on the final competency examination should be done.Keywords: Medical education, OSCE, pharmacotherapy, prescribingPembelajaran Farmakoterapi Integratif dengan Objective Structured Pharmacotherapy ExaminationAbstrakMenulis resep yang benar merupakan salah satu kompetensi dokter. Penelitian menunjukkan kesalahan medikasi masih menjadi masalah besar di pelayanan kesehatan dan banyak upaya sudah dilakukan untuk mengurangi hal tersebut melalui pelatihan. Farmakoterapi integratif adalah sebuah modul yang diberikan kepada mahasiswa kedokteran saat kepaniteraan klinis. Modul ini merupakan hasil adopsi dan dikembangkan dari World Health Organization Guide to Good Prescribing. Tujuan studi ini adalah untuk melihat efek nilai pra-uji dan pasca-uji dengan 17 kasus klinis. Studi dilaksanakan di Fakultas Kedokteran Universitas Kristen Indonesia, Jakarta Timur pada Juli-November 2018. Delapan puluh satu subjek secara acak dipilih dari data 200 mahasiswa berdasarkan kriteria eksklusi. Terdapat peningkatan nilai pasca-uji yang signifikan dibandingkan nilai pra-uji dari 42,07±12,45 ke 58,47±8,54 (p=0,000; CI -19,36; -13,45). Terdapat 69 (>85%) mahasiswa yang memiliki nilai D dan E pada pra-uji, namun angka tersebut turun pada pasca-uji menjadi 18 orang (22,2%) dari jumlah total 81 mahasiswa. Mahasiswa dengan nilai C meningkat dari 13,5% menjadi 70,4%, dan mahasiswa dengan nilai B dari 1% menjadi 7%. Mayoritas mahasiswa pada penelitian ini baru pertama kali mengikuti kepaniteraan klinik sehingga nilai pra-uji yang diperoleh sangat rendah karena belum memiliki pengalaman klinis. Namun, di akhir kepaniteraan, terdapat peningkatan pengetahuan dan penulisan resep terhadap beberapa jenis penyakit yang signifikan. Perlu dilakukan studi jangka panjang untuk mengukur retensi dan keberhasilan mereka di ujian akhir kompetensi.Kata kunci: Farmakoterapi, OSCE, pendidikan kedokteran, penulisan resep